PENINGKATAN PRODUKTIVITAS PENGERAJINANYAMAN SURYA PALM DAN CAHAYA PALM - Pandawani, Ni Putu; Parwita, Gde Bayu Surya; Paramita D., Putu Ayu (Ngayah: Majalah Aplikasi IPTEKS, 2019)
UD. Surya Palm is about 20 km to the east of Denpasar, namely in Banjar Kertiyasa, Bona Village, Blahbatuh District, Gianyar Regency, Bali. UD. UD. Surya Palm as a program partner SME is a small business engaged in crafting a variety of woven ornaments with the main raw material of mendong rope with woven models produced including lamp ornaments, model ornaments in various forms namely the shape of dogs, giraffes, horses, pigs and elephants. Palm Light is 23 km to the east of Denpasar, namely in the Banjar Pasedana, Bona Village, Blahbatuh District, Gianyar Regency, Bali. UD. Cahaya Palm as a program partner SME is a small business engaged in the craft of various woven bags and wallets with the main raw materials of palm leaves and pandanus. The second product of the UKM has not only been marketed in Bali and Java, but has also become an export commodity to the destination countries, namely the Netherlands, Australia, Britain, Japan and Hawaii.The problems faced in developing handicrafts are very varied starting from human resources and competencies of craftsmen, technology, marketing, capital, including sources of raw materials, "From the results of team observations, it appears that the two SMEs, for the sake of sustainability, are very worthy of coaching and assistance from the government in this case the Ministry of Research, Technology and Higher Education through Higher Education on an ongoing basis so as to increase production capacity and quality The purpose of this program is to be able to assist craftsmen in overcoming obstacles faced in developing their business. which is quite large on the quality of products and work productivity of SMEs and provides immediate benefits, namely the high motivation and enthusiasm of SME managers in advancing businesses so that later they become SMEs capable of producing products nationally and internationally and finally can contribute to increasing production, quality and turnover respectively.